Taxonomic review of the genus Periphyllus (Hemiptera, Aphididae, Chaitophorinae) in South Korea, with description of a new species - Ko, Jun Hyeok; Han, Taeman; Lee, Seungwhan; Lee, Wonhoon (Journal of Asia-Pacific entomology, 2024)
[Display omitted] •Taxonomic review of the genus Periphyllus in Korea.•One new species, Periphyllus peninsulasp. nov.•Acer pseudosieboldianum. A taxonomic review of the genus Periphyllus in South Korea is presented. This genus is represented by eight species in South Korea, including a new species, Periphyllus peninsulasp. n., collected from Acer pseudosieboldianum (Pax) Kom. Samples of aphids were collected from Acer spp. from several regions of South Korea, processed, preserved and studied using microscopic and photographic observations. Descriptions and illustrations of the eight species and a revised key for the identification of the new Korean species of Periphyllus are provided.